Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1159/000347218
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GPR39 Receptor and Ghrelin Receptor in Thyroid Tissues in Paediatric Patients with Immune and Non-Immune Thyroid Diseases

Abstract: The preproghrelin gene is responsible for generating ghrelin and obestatin, two gastric peptides with opposite effects on food intake. Obestatin suppresses food intake and digestive motility through interaction with GPR39 (GPCR). Ghrelin is supposed to be a link connecting metabolism and energy homeostasis with growth as the result of activation of the growth hormone secretagogue receptor (GHSR).The aim of the current study was to assess the expression of preproghrelin, GPR39 and GHSR in thyroid tissues from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The alimentary tract and human adipose tissue constitute an important part of the endocrine system, producing the greatest amounts of regulatory peptides. Food intake control is substantially regulated by the hypothalamic neurons that receive various signals from the so-called circuit-adipose tissue, stomach, intestines, thyroid, or pancreas [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The alimentary tract and human adipose tissue constitute an important part of the endocrine system, producing the greatest amounts of regulatory peptides. Food intake control is substantially regulated by the hypothalamic neurons that receive various signals from the so-called circuit-adipose tissue, stomach, intestines, thyroid, or pancreas [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…mRNA expression for preproghrelin was found in thyroid tissues, which is a proof of ghrelin gene-derived peptide presence in thyroid tissues. Therefore, we concluded that the expression of the ghrelin receptor family in thyroid tissues may suggest a role of gastric peptides in thyroid functions [9]. This was a starting point of the current study.…”
Section: Discussionmentioning
confidence: 72%
“…It is therefore possible that the association between these SNPs and autoimmune thyroid disorders is due to variations in the obestatin and ghrelin, as their role was shown in our previous study [9]. To our knowledge, it is a first study, where polymorphisms of preproghrelin in relation to AITDs are analyzed.…”
Section: Introductionmentioning
confidence: 77%